Life cycle analysis of graphene in a supercapacitor application - Cossutta, Matteo (2016)
The aim of this thesis is to undertake a life cycle analysis to identify the environmental impact of using graphene to manufacture supercapacitors. It was part of a larger project to develop supercapacitors using graphene in place of activated carbon.